Wireless Technology for Monitoring Site-specific Landslide in Vietnam - Gian Quoc-Anh; Nguyen Dinh-Chinh; Tran Duc-Nghia; Tran Duc-Tan; Kieu Nguyen Thi; Kumbesan Sandrasegaran (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Climate change has caused an increasing number of landslides, especially in the mountainous provinces of Vietnam, resulting in the destruction of vital transport and other infrastructure. Current monitoring and forecasting systems of the meteorology department cannot deliver accurate and reliable forecasts for weather events and issue timely warnings. This paper describes the development of a simple, low cost, and efficient system for monitoring and warning landslide in real-time. The authors focus on the use of wireless and related technologies in the implementation of a technical solution and some of the problems of the wireless sensor network (WSN) related to power consumption. Promising compressed sensing (CS) based solution for landslide monitoring is discussed and evaluated in the paper.